Assessing the Impact of the 2020 Council of State and Territorial Epidemiologists Case Definition for Pertussis on Reported Pertussis Cases - Rubis, Amy B; Cole, Matthew; Tondella, M Lucia; Pawloski, Lucia C; Youngkin, Erin; Firmender, Patricia; Aden, Vanessa; Cruz, Victor; Stanislawski, Emma; Wester, Rachel; Cieslak, Paul R; Acosta, Anna M; et al. (Clinical infectious diseases, 2024)
In 2020, the Council of State and Territorial Epidemiologists (CSTE) pertussis case definition was modified; the main change was classifying polymerase chain reaction (PCR)-positive cases as confirmed, regardless of cough duration. Pertussis data reported through Enhanced Pertussis Surveillance (EPS) in 7 sites and the National Notifiable Diseases Surveillance System (NNDSS) were used to evaluate the impact of the new case definition. We compared the number of EPS cases with cough onset in 2020 to the number that would have been reported based on the prior (2014) CSTE case definition. To assess the impact of the change nationally, the proportion of EPS cases newly reportable under the 2020 CSTE case definition was applied to 2020 NNDSS data to estimate how many additional cases were captured nationally. Among 442 confirmed and probable cases reported to EPS states in 2020, 42 (9.5%) were newly reportable according to the 2020 case definition. Applying this proportion to the 6124 confirmed and probable cases reported nationally in 2020, we estimated that the new definition added 582 cases. Had the case definition not changed, reported cases in 2020 would have decreased by 70% from 2019; the observed decrease was 67%. Despite a substantial decrease in reported pertussis cases in the setting of coronavirus disease 2019 (COVID-19), our data show that the 2020 pertussis case definition change resulted in additional case reporting compared with the previous case definition, providing greater opportunities for public health interventions such as prophylaxis of close contacts.